Endoscopic submucosal dissection of a duodenal lesion by using a novel adjustable traction device: A‐TRACT‐2. Issue 1 (25th October 2022) - Masgnaux, Louis‐Jean; Jacques, Jérémie; Pioche, Mathieu
Abstract : Watch a video of this article.